Islamic Fiscal Policy and Its Impact on Addressing Public Budget Deficits: An Applied Analytical Study - Musaab Mohammed Sayel Alamheedy (Research Parks Publishers, 2026)
One of the most visible issues affecting a lot of modern economies is public budget deficit, particularly in developing economies with low public revenues and high public spending. Increasingly, traditional financing tools that are based on loans are being relied upon, and there is a need to seek out more sustainable and equitable sources of financing. The purpose of this research is to analyze the role of Islamic financial policy in solving the public budget deficit problem by examining the most important tools of Islamic financial policy such as Zakat, Waqf, Islamic sukuk and other financial resources which can assist in supporting public revenues and decrease the tension on public balance. The research used descriptive-analytical method in studying the theoretical foundation of Islamic financial policy as well as Applied Analysis method in estimating potential contribution of some of the Islamic financial policy tools to the reduction of the budget deficit. The research has come to some conclusions, the most important of which is that the implementation of Islamic financial policy tools can contribute effectively in improving public revenues, lessening the pressure of government spending in certain social sectors and offering alternative financing mechanisms based on the concept of justice and economic solidarity. In addition, the study suggests the requirement of creating institutional and legislative structures and supporting the application of Islamic financial instruments in the current financial policy.